Pengaruh pemberian mata kuliah Psikologi pengembangan diri terhadap Self Confidence pada mahasiswa semester pertama Fakultas Psikologi Universitas Tarumanegara - Untung Subroto; Linda Wati; Febrianto Febrianto (Provitae: Jurnal Psikologi Pendidikan, 2022)
This research is motivated by the phenomenon of first semester students who have problems adapting to educational conditions due to changes in the learning system and environment during the pandemic which makes students feel stressed and not confident in taking education. Therefore, a method is needed that can make students more confident, one of which is by increasing the knowledge of students themselves through the Psychology of Self-Development course. This study aims to examine the effect of giving psychology courses on self-development to first-semester students. This study used a quasi-experimental method with a pretest-posttest technique. The subjects of this study consisted of 17 men and 108 women. Measurements in this study used the Paired Sample T-Test, where the results of the test showed a significance value of less than 0.05 (0.00) which indicated a significant difference between the pretest score and the post-test score. So it can be said that presenting the Psychology of Self-Development course is a method used to assist students in increasing Self-confidence. Thus, there is an influence between presenting the self-development course on the self-confidence of the first semester students of the Faculty of Psychology, Tarumanegara University.